Citizenship campaigns as community civics to strengthen civic engagement - Pradana, Yudha; Darmawan, Cecep; Rahmat; Anggraeni, Leni (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This research aims to reflect on citizenship campaigns as a means of community civics to strengthen civic engagement through a qualitative approach and phenomenological methods. Participant reflections emphasize how civic engagement manifests in civic activity and political voice through community civics, particularly concerning the socio-cultural dimensions of civic education, which align with the goals of fostering smart and good citizenship. Civic activity is associated with philanthropic movements, while political voice relates closely to political aspirations aimed at influencing policy. This reflection on citizenship campaigns serves as a channel for community civics, enhancing civic engagement in the form of both civic activity and political voice related to the public good and public interest. Campaigns can act as tools for persuasion and the dissemination of ideas that promote the development of citizen attributes. Furthermore, this study enriches the understanding of civic communication which is intrinsically linked to how citizens behave, engage, and participate in civic issues relating to the meaning of aspects of communication and use of media.